In elderly individuals, the effectiveness of sensorimotor training on postural control and muscular strength is comparable to resistance-endurance training - Varjan, Mikuláš; Žiška Böhmerová, Ľubica; Oreská, Ľudmila; Schickhofer, Peter; Hamar, Dušan (Frontiers in Physiology, 2024)
While classical resistance exercise is an effective way to improve strength and control postural sway, it may not be suitable for some elderly individuals with specific health disorders (e.g. aneurysms). Therefore, there is a need to explore alternative modalities. The study aimed to evaluate the effects of sensorimotor training on muscle strength and postural control in the female elderly population and subsequently compare these effects with a traditional combined resistance-endurance training program. A total of 34 healthy, active elderly women aged from 65 to 75 years, (average age 72.7±4.4 years, height 161.6±5.1 cm, and weight 66.9±8.4 kg) were randomly assigned to three groups undergoing different 10-week interventions: the resistance-endurance training (RET, n=11), the sensorimotor training (SMT, n=12) and the control group (COG, n = 11). Prior to and after the interventions all participants underwent tests of maximal voluntary contraction of the dominant and non-dominant leg; postural sway tests with open and closed eyes; novel visual feedback balance test; 10-meter maximal walking speed (10mMWS) and stair climb test. A T-test and repeated measures ANOVA were used, followed by the Bonferroni post hoc test, to compare the pre and post-measurements and assess differences in gains between groups. Results showed a significant main effect of time on strength (p<0.001). In addition, significant differences in time x group interaction on strength (p<0.01), postural control (p<01), and ascendant and descended vertical speed (p<0.001) were observed. Besides, the RET group improved significantly the maximal voluntary contraction of both dominant (16.3%, p≤0.01) and non-dominant leg (10.9%, p≤0.05). SMT group improved maximal voluntary contraction of both dominant (16.6%, p≤.001) and non-dominant leg (12.7%, p≤.01). In addition, they also improved mean velocity of the centre of pressure (COP) in postural sway test with eyes open (24.2%, p≤0.05) as well as eyes closed (29.2%, p≤0.05), mean distance of COP in novel visual feedback balance test (37.5%, p≤0.001), ascendant and descended vertical velocity (13.6%, p≤0.001 and 17.8%, p≤0.001, respectively). Results show not only resistance training but sensorimotor intervention boosts strength too. This intervention also enhances postural control and functional abilities for both ascending and descending movements.